Iceland’s External Affairs from 1550-1815: Danish societal and political cover concurrent with a highly costly economic policy - Þórhallsson, Baldur; Joensen, Tómas (Stjórnsýslustofnun, 2014)
The paper argues that there is not necessarily a correlation between political, economic and societal shelter. Iceland received considerable societal and political shelter from Denmark in the period under study, but Denmark failed to provide its remote island with economic cover. Firstly, and most importantly, it provided substantial and highly valuable societal shelter. Copenhagen was the main channel by which new knowledge and technology could enter Iceland. The islanders benefited from educational, health-care and social policies of the crown and it played an invaluable role in preserving Iceland’s cultural heritage. Secondly, Denmark provided partial protection of Icelandic waters and land though Iceland’s peripheral position continued to be its main protection from outside attacks. However, at the end of our period, the Danish kingdom was in decline and unable to provide political cover. Nevertheless, increased centralization, initiated from Denmark, provided internal order and political stability and citizens became more equal before the law. Thirdly, Icelanders paid a heavy price for the Danish trade monopoly though Icelanders continued to receive partial economic and societal shelter from foreign merchants and fishermen. The crown’s policies towards Iceland can largely be explained by current ideological trends at any given time. By being in constant contact with the European continent through Denmark, Icelandic society was part of the societal, political and economic evolution in Europe and managed to avoid isolation despite its geographical remoteness.